Building management and innovation capabilities for global health: a senior executive program - Prado, Andrea M.; Sánchez-Gómez, Jose Ignacio; Casamitjana, Núria; Espriu, Marina; Kumar, Pratap; Ngoye, Ben; Bärnighausen, Till; Rosenmoller, Magda (Frontiers in Public Health, 2023)
Accurately approaching the major challenges associated with global health management has become a mandatory key point in the training of medical leaders around the world. The Senior Executive Program in Global Health Innovation Management (SEPGHIM) seeks to provide an answer to the need for innovation and managerial capacity building in Global Health and to address the current detachment between Public Health Organizations and Business Schools. In 2019, SEPGHIM's first edition was led by five prestigious academic institutions on three continents. The first cohort included a total of 27 high-level health professionals and executives from 16 countries with 7-10 years of working experience who participated during the 11 months of the course. The program sought to fill an often-found knowledge gap among health professionals in terms of health innovation, leadership, and management. SEPGHIM relied on multiple pedagogical methods conveyed through a robust theoretical and applied syllabus that included case studies, simulations, guest speakers, debates, site visits, and an executive challenge. The program achieved various results. First, it recruited high-level health professionals that ensured diversity of backgrounds, allowing an exchange of experiences and different ways of addressing global health challenges. Second, it created a network of health professionals for possible future collaborations that can anticipate new trends and opportunities in global health and work together with stakeholders from other sectors. This networking was one of the most highly rated benefits by the students. Finally, the participants expressed great eagerness to recommend the program (4.9 out of 5) to other decision-makers and leaders in the global health field. These results provide positive insights regarding the value of such a training program for senior health professionals.